RETRACTED M-HEALTH SERVICES: CAN IT BE A POTENTIAL MECHANISM IN IMPROVING PUBLIC HEALTH SYSTEM OF INDIA? - Davey, Sanjeev; Davey, Anuradha; Singh, Jai Vir; Raghav, Santosh Kumar (Indian Journal of Community Health, 2013)
Background: The role of mobile in health system is now important for us, to make use of this very fastly growing technology in improving the public health of Indian people. Objectives: To critically review the role of m-health in public health system of India. Methods: A systematic review of related studies and literature of last 10 years published in pubmed etc till 31st March 2013 on role of m-Health in public health was done. Results and discussion: A wide variety of m-health applications are available in mobile phone market, needing proper regulation from health care authorities and with a hope of better future results. Recommendations: We must use these applications weighing their benefits and utility in public health as well as capitalizing the better prospect of m-health worldwide in the field of public health. This can give a greater access to larger segments of a rural and underserved population in developing countries like India with a hope of improving the capacity of health system to provide quality healthcare to Indian people.